Synthesis of Imidazole-Compound-Coated Copper Nanoparticles with Promising Antioxidant and Sintering Properties - Yu Zhang; Xianchong Yu; Ziyuan Chen; Song Wu; Haiqi Lai; Shiwo Ta; Tingyu Lin; Guannan Yang; Chengqiang Cui (Micromachines, 2023)
In this study, we present a facile method for preparing oxidation-resistant Cu nanoparticles through a liquid-phase reduction with imidazole compounds (imidazole, 2-methylimidazole, 2-phenylimidazole, and benzimidazole) that serve as protective and dispersing agents. Through a complexation reaction between Cu atoms, the imidazole compounds can form a protective film on the Cu nanoparticles to prevent the particles from rapidly oxidizing. We compared the effects of the four kinds of imidazole compounds on the oxidation resistance and sintering properties of Cu particles. The Cu particles prepared with benzimidazole could be stored in the air for 30 days without being oxidized. After sintering at 300 °C and 2 MPa, the joint of the particles could reach a shear strength of 32 MPa, which meets the requirements for microelectronic packaging.